The PD-1/PD-L1 Pathway Affects the Expansion and Function of Cytotoxic CD8+ T Cells During an Acute Retroviral Infection - David, Paul; Megger, Dominik A.; Kaiser, Tamara; Werner, Tanja; Liu, Jia; Chen, Lieping; Sitek, Barbara; Dittmer, Ulf; Zelinskyy, Gennadiy (Frontiers in Immunology, 2019)
Cytotoxic CD8+ T lymphocytes (CTL) efficiently control acute virus infections but can become exhausted when a chronic infection develops. The checkpoint receptor PD-1 suppresses the functionality of virus-specific CD8+ T cells during chronic infection. However, the role of the PD-L1/PD-1 pathway during the acute phase of infections has not been well characterized. In the current study the effects of PD-1 or PD-L1 deficiency on the CD8+ T cell response against Friend retroviral (FV) infection of knockout mice was analyzed during acute infection. We observed an enhanced proliferation, functional maturation, and reduced apoptosis of effector CD8+ T cells in the absence of PD-1 or PD-L1. The knockout of PD-L1 had a stronger effect on the functionality of CD8+ T cells than that of PD-1. Augmented CTL responses were associated with an improved control of FV replication. The strong phenotype of FV-infected PD-L1 knockout mice was independent of the interaction with CD80 as an additional receptor for PD-L1. Furthermore, we performed a detailed analysis of the production of different granzymes in virus-specific CD8+ T cells and observed that especially the simultaneous production of multiple granzymes in individual T cells (multifunctionality) was under the control of the PD-1/PD-L1 pathway. The findings from this study allow for a better understanding of the development of antiviral cytotoxic immunity during acute viral infections.